Re-Humanizing Architecture : New Forms of Community, 1950-1970 - Hopfengärtner, Judith; Moravánszky, Ákos (East West Central : Re-building Europe 1950-1990, 2016)
After the Second World War, a divided Europe was much affected by a period of reconstruction. This was influenced by the different political systems – in the socialist East and in the capitalist West, the focus was on cohesion in society and its cultural and architectural expression. In parallel to the rapidly progressing industrialization of the building industry, debates on the humanization of the built environment were led on both sides with great intensity. The volume shows how, on the back of existentialism, new monumentality, and socialist realism, quite similar concepts and strategies were developed in order to find answers to questions relating to adequate structures for new forms of community and identity.